Nafkah Suami Kepada Keluarga Dalam Hadits Da’if Nomer 115 Bab 96 Teori Simultan Dan Parsial Adabulmufrad - Mohammad ruslan (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2020)
This paper aims to discuss about hadis classifiedas da’if by al-Bani in his book Da’if Adabul Mufrad al- Imam Bukhari based on hadis analysis about basic necessities of husband to his family, as stated in hadis 96 no 115. This hadis is classified as hadis mauquf because al-Rajul referred to Sahabi, when the writer traced the hadis based on simultaneous analysis, this hadis classified as hadis dha’if by al-Bani is absolutely correct. The hadis text is not considered shad or contradicted to the history ofthe Quran. So It is s ahihul matan. But the writer found any other aspect of rawi like Ismail bin Rofi' and clasified as Majhul like al-Walid. Keywords: Simultaneous analysis, d}a>if Adabul Mufrad, basic necessities of husband